Determination of the optimum conditions and effect of some environmental stresses on seed germination and seedling growth of chard plant (Beta vulgaris var. cicla) - Nadia Bahremand (تنش های محیطی در علوم زراعی, 2018)
Introduction Biotic and abiotic stresses has always been a concern in agriculture.The response of plants to inevitable environmental stresses in various stages of growth and development, will be a good strategy for plants initial assessment in confronting with adverse conditions and their productivity. In situation of the food crisis, vegetables increased production as a relatively cheap source to provide the daily needs of people to vitamins, minerals and active compounds against cancer and premature aging has been considered by many researchers. Identify the expectation or tolerance of plants and use of this capacity in unfavorable conditions is one of the primary ways when we have no choice sa saline soils or overpopulation. Chard plant (Beta vulgaris var. Cicla), belonging to Amaranthaceae family, that its effectiveness properties in reducing heart attacks, diabetic, colon and prostate cancer has been proven can be examined. Increasing production by creating conditions free of tension, especially in the early stages of plant growth is possible. Irreparable damages of plants production amount by biotic and abiotic stresses in the environment is always observed. This study aimed to determine the optimal conditions and effect of some environmental stresses such as salinity, drought and temperature on seed germination and seedling growth of chard plant. Matherials and methods Some separate trials as completely randomized design (only drought and temperature as factorial) with three replication in horticulture laboratory of University of Jiroft was conducted.The effect of constant temperatures, alternating temperatures, hydropriming, salinity, acidity and drought stresses on germination indexs such as germination percentage, germination speed, seed vigor, seedling growth and chemical compositions of plant changing (proline content and antioxidant enzymes activity) under some stresses were measured. Results and discussion The results of this search showed that minimum temperature during seed germination 1.92±1.24, optimum 25±0.74 and maximum were 45.84±1.67°C. The maximum germination rate was observed in alternating temperature 20/100C. 18-hour hydropriming (washing with running water) of seed compared to control had an significant effect on germination seed. (P